Changhsingian (Lopingian, Permian) radiolarian paleobiogeography on and around the Yangtze Platform - Xiao, Yi-Fan; Wang, Kai-Yue; He, Wei-Hong; Suzuki, Noritoshi; Zhang, Ke-Xin; Yang, Ting-Lu; Wu, Shun-Bao (Palaeoworld, 2024)
We report a Changhsingian radiolarian assemblage from the Rencunping section of the Dalong Formation, in the northern margin of the Yangtze Platform, South China. The assemblage is composed of 37 species belonging to 20 genera, including two new species (Copicyntroides rencunpingensis n. sp. and Copicyntroides subplanus n. sp.). Together with the well documented radiolarian faunas of the Dalong Formation around the Yangtze Platform, we applied Sørensen Coefficient, an incidence-based measures of relative similarity, to examine the similarity of species associations among the sections of the Dalong Formation, including those at Rencunping, Shangsi, Hushan, Pingdingshan, Xinmin and Dongpan. We find that 165 species have been reported in the entire Dalong Formation of all sections, with variable paleobiogeographic setting from section to section within the same formation. The Sørensen Coefficient showed a high similarity between the Rencunping and Pingdingshan sections and low similarity in the Xinmin or Dongpan sections. This is interpreted as due to water mass separation between the northern and southern sides of the Yangtze Platform, probably by the physical barrier of the shallow carbonate platform in the region. We reviewed taxonomic groups and depositional conditions in each section, and determined “low latitudinal common species” or “cosmopolitan” species including Entactinia itsukaichiensis, Albaillella angusta, A. excelsa, A. protolevis, A. triangularis, Ishigaum obesum, I. trifustis, Trilonche crassispinosa, Triplanospongos musashiensis and “Hegleria-shaped” radiolarian. The radiolarian fauna of Rencunping was concluded as a typical fauna in the Dalong Formation, and its higher similarity to faunas from Japanese Islands and Southeast Asia indicates close paleogeographic positions and similar paleogeographic environments in these areas during the Changhsingian.